A Research on Quality control practices in Indian construction Industries using statistical Analysis (International Journal of Food and Nutritional Sciences, 2022)
The main objective of the study was to investigate the existing practices in quality control of construction companies in India and, to determine a relation between the extent of quality control to the Net Worth of the company using statistical methods. Quantitative analysis was done to identify